SYSTEMATIC REVIEW: EPIDEMIOLOGY OF LEPTOSPIROSIS IN INDONESIA - Dewi Yuniasih; Nuni Ihsana; Dhea Arinda Shalsabila; Novi Wijayanti Sukirto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The burden of global leptospirosis is very significant; However, inadequate diagnosis has affected disease awareness in the medical community. This systematic review aims to find the leptospirosis rates more accurately and to increase early awareness of leptospirosis with the prevention and control of leptospirosis programs in Indonesia. The method of this paper is a systematic review with the result of 447 article titles from Google scholar and Pubmed which be accessed. Leptospirosis cases mostly occur in people adults in the age group 20-50 years, male, and working as a farmer. The suggestions put forward are to do a more in-depth analysis to answer the formulation and objectives of the research.